Characterization of Patients with Oral Cancer and its Relationship with Invasion in Depth - José Daniel Gil Milá; Johannes René Maestre Cabello; Karen Martínez Gómez (Universidad de las Ciencias Médicas de Cienfuegos, 2021)
Background: oral cancer is a challenge for any health system, integrating deep invasion as a factor, along with tumor size, allows effective staging and treatment. Objective: to characterize patients treated at the Institute of Oncology and Radiobiology who underwent oral cavity surgery and to corroborate the prognostic factor of the depth of invasion. Method: a descriptive, cross-sectional study was carried out in a series of cases in the Head and Neck Service of the Oncology and Radiobiology Institute, from January 2018 to December 2019. The data were obtained in the medical records; the statistical package SPSS 15.0 was used. The variables used were: age, sex, location and size of the tumor, lymph node metastasis, lymph node levels, treatment, current status, degree of differentiation, extranodal extension. Descriptive statistics procedures were used; the results are presented in tables of frequency and relation of variables in numbers and percentages. Results: the most frequent age range was between 51-60 years old. The tongue was the most affected site, with a moderate degree of differentiation. There was a direct relationship between hidden lymph node metastasis and invasion in depth, demonstrating a direct proportionality between greater depth of invasion and the presence of lymph node metastases in the pathologist's evaluation. Conclusions: the ages over 50 years old and the male sex were the most vulnerable to suffer from oral cancer, the tongue was the most affected anatomical site. There was a direct relationship between hidden lymph node metastasis and deep invasion.